2016
DOI: 10.1073/pnas.1516011113
|View full text |Cite
|
Sign up to set email alerts
|

The role of ions in the self-healing behavior of soft particle suspensions

Abstract: Impurities in crystals generally cause point defects and can even suppress crystallization. This general rule, however, does not apply to colloidal crystals formed by soft microgel particles [Iyer ASJ, Lyon LA (2009) Angew Chem Int Ed 48:4562-4566], as, in this case, the larger particles are able to shrink and join the crystal formed by a majority of smaller particles. Using small-angle X-ray scattering, we find the limit in large-particle concentration for this spontaneous deswelling to persist. We rationali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
187
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(213 citation statements)
references
References 48 publications
(31 reference statements)
24
187
2
Order By: Relevance
“…Recently, we have presented a model for this selective deswelling at high concentrations [14] and have shown that the freezing point of polydisperse and bidisperse pNIPAM suspensions is directly linked to particle deswelling [6]. Our findings suggest that the counterions associated to the charged groups at the periphery of pNI-PAM microgels and the osmotic pressure they exert at high particle concentrations are the key to the deswelling behavior.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…Recently, we have presented a model for this selective deswelling at high concentrations [14] and have shown that the freezing point of polydisperse and bidisperse pNIPAM suspensions is directly linked to particle deswelling [6]. Our findings suggest that the counterions associated to the charged groups at the periphery of pNI-PAM microgels and the osmotic pressure they exert at high particle concentrations are the key to the deswelling behavior.…”
Section: Introductionmentioning
confidence: 71%
“…When these overlap-regions take most of the space between particles and percolate through the suspension volume, the previously bound counterions become free to explore the space between the particles, hence contributing to the osmotic pressure of the suspension which, therefore, increases. In our previous work [14], we showed with simple Monte-Carlo simulations that the osmotic pressure due to those counterions outside the particles is indeed higher than that inside the particles for φ 0.5. The counterion concentration inside the particles does not increase with φ, as the electrostatic conditions there are mostly unaffected provided the configuration of fixed charges in the particle periphery stays fixed.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…core-shell. 9,13 Microgel particles are very promising with respect to applications in biomedical devices 14,15 , as sensors 16,17 , for drug delivery [18][19][20][21][22][23] , as functionalized and possibly double responsive microgels for nanoreactors [24][25][26][27] , and in colloidal crystals [28][29][30][31][32][33][34] .…”
Section: Introductionmentioning
confidence: 99%